Targeting Alzheimer's disease with novel dual-function 3,5-diaryl-4,5-dihydro-1H-pyrazole-1-carbothioamide derivatives - Aikaterini Katsogiannou; Danai Karta; Antonio Di Stefano; Sena Oner; Mehmet Enes Arslan; Adil Mardinoglu; Hasan Turkez; Stamatia Vassiliou; Ivana Cacciatore (European Journal of Medicinal Chemistry Reports)
In the field of medicinal chemistry, the versatility of the thiosemicarbazone scaffold makes it a promising platform for the development of next-generation pharmaceuticals. In this paper the thiosemicarbazone scaffold was explored to obtain novel series of derivatives: a) thiosemicarbazones 15–31, and 33 containing a linear thiosemicarbazone scaffold, b) 34–38 and 44–64 containing pyrazoline ring, and c) 39–43 containing the dihydropyrimidine cycle. Among these, compounds 21, 23, 26, 33–35, 37, 38, 44, 57, 61, and 62 demonstrated no significant cytotoxic effects on HDFa cells at concentrations up to 500 μg/mL. Importantly, compounds 21, 23, 26, 33, 34, 35, and 37 exhibited significant protective effects against neurotoxicity induced by beta-amyloid peptide (1-42) in differentiated SHSY-5Y cell cultures. Enzymatic assays targeting BACE1 and AChE revealed modest inhibitory activity in compounds 21, 23, and 34, 37, respectively. The identification of compounds with inhibitory effects and neuroprotective activity against beta-amyloid peptide (1-42) offers a platform for further optimization and refinement of these compounds to enhance their potency and selectivity.